Daring to build fair and sustainable urban food systems: A case study of alternative food networks in Australia. Issue 3 (16th March 2021) - Canal Vieira, Leticia; Serrao-Neumann, Silvia; Howes, Michael
ABSTRACT: Food systems are under pressure from population growth, climate change, resource scarcity and increasing urbanization. Alternative food networks are initiatives related to food provision that operate at a local level and are concerned with both environmental stewardship and social justice. This paper presents a case study of alternative food networks operating in Brisbane and Melbourne in order to analyze: i) their socio-economic and environmental contributions to the resilience and sustainability of urban food systems; and, ii) the limitations that alternative food networks are facing. The cases researched include examples of urban agriculture, food hubs, buyers' groups, and specialist retailers. The results indicate that alternative food networks can improve access to healthy food, provide fairer conditions for farmers, reduce food loss/waste, increase environmental protection, and facilitate climate change adaptation. The limitations to the expansion of alternative food networks are also discussed, including the restricted access to land for growing food, low public engagement, and the dependence on volunteer labor. The paper concludes by summarizing the contribution of alternative food networks to urban food systems and identifies issues for future research.